Редуктор на базе передачи с промежуточными телами качения с двусторонним выходом ведомого вала - Ефременков Е. А. Егор Алексеевич; Шибинский К. Г. Константин Григорьевич; Кобза Е. Е. Евгений Евгеньевич
опубл. 20.03.10, Бюл. № 8